2020
DOI: 10.4240/wjgs.v12.i8.336
|View full text |Cite
|
Sign up to set email alerts
|

Influence of postoperative complications on long-term survival in liver transplant patients

Abstract: BACKGROUND Liver transplant (LT) is a complex procedure with frequent postoperative complications. In other surgical procedures such as gastrectomy, esophagectomy or resection of liver metastases, these complications are associated with poorer long-term survival. It is possible this happens in LT but there are not enough data to establish this relationship. AIM To analyze the possible influence of postoperative complications on long-term survival and the ability of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…We extended the evaluations to 1 year and longer follow-up times, consistent with other recent studies. 16 Cutoff CCI value of 42 was identified as a significant predictor of overall mortality consistent previous studies. The rate of complication and CCI were similar in both cohorts in 1 year and overall results.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We extended the evaluations to 1 year and longer follow-up times, consistent with other recent studies. 16 Cutoff CCI value of 42 was identified as a significant predictor of overall mortality consistent previous studies. The rate of complication and CCI were similar in both cohorts in 1 year and overall results.…”
Section: Discussionsupporting
confidence: 88%
“…Also, 2 cohorts of PSC patients were compared: those with end-stage liver disease and those with premalignant findings, but better liver function. We extended the evaluations to 1 year and longer follow-up times, consistent with other recent studies 16 . Cutoff CCI value of 42 was identified as a significant predictor of overall mortality consistent previous studies.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, Staiger et al, in a population of 479 patients undergoing major general surgery including LT, outlined that the CCI can be a useful warning signal for overall high morbidity by 90 days [ 9 ]. Finally, Castanedo et al, in a study of 164 LT patients where different score systems were assessed, showed that the CCI, as a measure of overall morbidity, was an independent negative predictive factor of long-term survival [ 10 ]. The sum of all of these observations suggests the CCI as a useful tool for objectively alerting caregivers to any worsening of patients’ clinical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, in the effort to increase the donor pool, uncommon types of LT donors have been increasingly considered in recent years with a growing number of LT procedures using liver grafts from DCDs and very old DBDs [ 3 , 4 ]. Interestingly, the literature focuses primarily on their long-term outcomes and only limited data are available about the perioperative period which, however, is increasingly recognized as relevant [ 1 , 5 , 9 , 10 ]. Therefore, after a preliminary balancing, we herein report and compare the operating theatre and Intensive Care Unit (ICU) courses of patients who received a LT from a DCD or a DBD aged ≥ 80 years.…”
Section: Introductionmentioning
confidence: 99%
“…After liver transplantation, patient survival depends on many different factors including graft function. In the initial phases, the successful function of the graft depends on hepatocyte function and vasculature recovery, whereas in the long term, complications such as nonanastomotic biliary strictures (NAS) can have a profound impact on graft and patient survival ( 1 , 4 , 5 ). NAS are characterized by the progressive loss of biliary tract architecture ( 6 ), frequently resulting in graft loss (45.8% requiring retransplantation) or death (25%) ( 7 ).…”
Section: Introductionmentioning
confidence: 99%